A retrospective-prospective review of Suzuki–Miyaura reaction: From cross-coupling reaction to pharmaceutical industry applications - Farhang, Mehran; Akbarzadeh, Ali Reza; Rabbani, Mahboubeh; Ghadiri, Amir Mohammad (Polyhedron, 2022)
The products of the Suzuki coupling reaction show significant advantages in the pharmaceutical industry. In this review, the biaryls products of the Suzuki reaction that indicate pharmaceutical properties are classified into eight groups. The continuous flow process shows more advantages than the Batch process because it makes high-quality products. [Display omitted] •The products of the Suzuki coupling reaction show significant advantages in the pharmaceutical industry.•In this review, the biaryls products of the Suzuki reaction that indicate pharmaceutical properties are classified into eight groups.•The continuous flow process shows more advantages than the Batch process because it makes high-quality products. Carbon-carbon coupling is the most important reaction in chemical, academia, and industrial scales. The Suzuki-Miyaura coupling is a cross-coupling reaction in which the coupling partners are an organoborane and an aryl halide to make biaryls as a product. Some important parameters such as metals, catalysts, solvents, and substrates can affect the Suzuki reaction. The products of the Suzuki coupling reaction show significant advantages in the pharmaceutical industry. The Suzuki coupling reaction can produce some drugs like losartan, valsartan, diflunisal, lapatinib, atazanavir, and clonazepam. In this review, the biaryls products of the Suzuki reaction that indicate pharmaceutical properties are classified into eight groups. These groups include benzodiazepines (BDZ), angiotensin receptor blockers (ARBs), non-steroidal anti-inflammatory drugs (NSAIDs), kinase inhibitors, protease inhibitors, and tryptophan hydroxylase (TPH) inhibitors, and B-cell lymphoma (BCL-2) inhibitors. Nowadays, producing drugs using a continuous flow process is a new method in the pharmaceutical industry. The continuous flow process shows more advantages than Batch or semi-Batch processes. Continuous flow chemistry is faster, safer, eco-friendly, and makes high-quality products.